Psychometrics assessment of ethical decision-making around end-of-life care scale for adolescents in the final stage of life - Mohammadi, Fateme; Masoumi, Seyedeh Zahra; Khazaei, Salman; Hosseiny, Seyyed Mohammad Mahdi (Frontiers in Pediatrics, 2024)
Introduction: Healthcare professionals have a critical role in ethical decision-making around end-of-life care. Properly evaluating the ethical decision-making of health care professionals in end-of-life care requires reliable, tailored, and comprehensive assessments. The current study aimed to translate and assess psychometrically a Persian version of the ethical decision making in end-of-life care scale for Iranian adolescents in the final stages of life.The present study investigates the methodology and multicenter research. 310 healthcare professionals who treat/care for adolescents at the end of life were selected from 7 cities in Iran. The original version of the end-of-life care decision-making scale was translated into Persian using the forward-backward translation method, and its psychometric properties were evaluated using COSMIN criteria.Results: Exploratory factor analysis revealed that the factor loadings of the items ranged from 0.68 to 0.89, all of which were statistically significant. Furthermore, three factors had eigenvalues greater than 1, accounting for 81.64% of the total variance. Confirmatory factor analysis indicated a proper goodness of fit in the hypothesized factor structure. The internal consistency reliability of the tool was assessed in terms of its homogeneity, yielding a Cronbach's alpha coefficient of 0.93.The Persian version of the End-of-Life Care Decision-Making Scale demonstrates satisfactory validity and reliability among healthcare professionals working with adolescents in the final stages of life. Therefore, nursing managers can utilize this tool to measure and evaluate ethical decision-making in end-of-life care for adolescents in the final stages of life and identify the most appropriate strategies, including educational interventions, to improve ethical decision-making in end-of-life care if necessary.